2023
DOI: 10.3390/ani13050889
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Inactivated Porcine Epidemic Diarrhea Virus Presenting in the Intestine Induces Mucosal Immunity in Mice with Alginate–Chitosan Microcapsules

Abstract: The porcine epidemic diarrhea virus, PEDV, which causes diarrhea, vomiting and death in piglets, causes huge economic losses. Therefore, understanding how to induce mucosal immune responses in piglets is essential in the mechanism and application against PEDV infection with mucosal immunity. A method of treatment in our research was used to make an oral vaccine that packaged the inactive PEDV with microencapsulation, which consisted of sodium alginate and chitosan, and adapted the condition of the gut in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous study found that the PEDV could activate the transcription of type I interferon in porcine monocyte-derived dendritic cells, and the PEDV did not replicate in the dendritic cells [ 37 , 46 ]. However, the E protein in the PEDV acts as an antagonist suppressing IFN-β through the RIG-I-mediated signaling in the host innate immune response of IPEC-J2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found that the PEDV could activate the transcription of type I interferon in porcine monocyte-derived dendritic cells, and the PEDV did not replicate in the dendritic cells [ 37 , 46 ]. However, the E protein in the PEDV acts as an antagonist suppressing IFN-β through the RIG-I-mediated signaling in the host innate immune response of IPEC-J2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%